Electrical installations in hazardous areas - McMillan, Alan. (Boston : Butterworth-Heinemann, 1998)
The Health and Safety at Work Act, together with current and impending EU Directives, obliges those responsible for hazardous areas, those who work in such areas and those who supply equipment for use in such areas to demonstrate that they have taken all necessary and reasonable steps to prevent fires and explosions. This book addresses these issues, seeks to explain the ever increasing complexity of standards and codes pertaining to this field and describes their method of application and the application of other procedures to assist those involved. The only book which provides comprehensive cover of this vital area. Written by a leading Internationally recognised UK authority in this field.
Introduction; Area classification; Area classification practice for gases, vapours and mists in freely ventilated situations; Calculation of release rates and the extents of hazardous areas; Area classification practice for gases, vapours and mists in areas which are not freely ventilated; Area classification practice for dusts; Design philosophy for electrical apparatus for explosive atmospheres; General requirements for explosion protected apparatus (gas, vapour and mist risks); Apparatus using protection concepts encapsulation 'm', oil immersion 'o' and powder filling 'q'; Apparatus using protection concept flameproof enclosure 'd'; Apparatus using protection concept pressurization 'p'; Apparatus using protection concept increased safety 'e'; Apparatus and systems using protection concept intrinsic safety 'i'; Apparatus using protection concept 'N' ('n'); Protection concepts for apparatus for dust risks; Other methods of protection and future apparatus requirements; Selection of power supply, apparatus and interconnecting cabling system for both gas/vapour/mist risks and dust risks; Installations in explosive atmospheres of gas, vapour, mist and dust; Installation of pressurized apparatus and other uses of the pressurization technique; Installation of intrinsically safe apparatus/associated apparatus and intrinsically safe systems 'i'; Documentation, inspection, test and maintenance of explosion protected apparatus, systems and installations; Radio frequency radiation and static electricity.
Includes bibliographical references and index.
Keywords: Explosionproof electric apparatus and appliances; Electric apparatus and appliances -- Safety measures; Hazardous substances -- Safety measures; Electronic books